2004
DOI: 10.1207/s15327876mp1604_3
|View full text |Cite
|
Sign up to set email alerts
|

The Capacity to Lead: Major Psychological Differences Between Leaders and Nonleaders

Abstract: This study returns to the question that occupied "trait approach" scholars in the early days of leadership research: identification of the major capacities required for leadership. The conceptual and methodological progress that has been made in psychology since the trait approach enables us to formulate models and deal with variables that did not exist in the early days of leadership research. We argue that three types of psychological capacities are essential for leadership: (a) self confidence, expressed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 45 publications
6
70
1
2
Order By: Relevance
“…A part of Hypothesis 1 was verified and was consistent with the results from other researchers (Mikulincer & Florian, 1995;Popper, 2002;Popper & Amit, 2009;Popper et al, 2004;Popper et al, 2000), indicating that early attachment history is important for personal workplace relationships. The results from the exploratory trials indicated that Hypotheses 2 and 3 were reasonable but that the connections to the task-oriented part of leadership were more complicated than expected.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A part of Hypothesis 1 was verified and was consistent with the results from other researchers (Mikulincer & Florian, 1995;Popper, 2002;Popper & Amit, 2009;Popper et al, 2004;Popper et al, 2000), indicating that early attachment history is important for personal workplace relationships. The results from the exploratory trials indicated that Hypotheses 2 and 3 were reasonable but that the connections to the task-oriented part of leadership were more complicated than expected.…”
Section: Discussionsupporting
confidence: 89%
“…This hypothesis is within the same area of leadership (the personal relationship between the leader and subordinates) in which previous studies (Mikulincer & Florian, 1995;Popper, 2002;Popper & Amit, 2009;Popper et al, 2004;Popper et al, 2000) have shown a connection.…”
Section: Hypothesesmentioning
confidence: 84%
“…Numerous studies have found associations between leadership effectiveness and secure attachment (Berson, Dan, & Yammarino, 2006;Englund, Levy, Hyson, & Sroufe, 2000;Mikulincer & Florian, 1995;Popper, Amit, Gal, Mishkal-Sinai, & Lisak, 2004;Sharf & Mayseless, 2009). Secure styles appear more adept at leadership positions, as self-confidence, sensitivity, prosocial attitude, and availability are qualities found in both secure individuals and good leaders (Popper & Mayseless, 2007).…”
Section: Leader-follower Relationshipsmentioning
confidence: 99%
“…Segundo alguns estudos (Popper & Mayseless, 2003;Popper, Mayseless, & Castelnovo, 2000, Popper, Amit, Gal, Mishkal-Sinai, & Lisak, 2004, os indivíduos com mais segurança estão melhor preparados do que os outros para se tornarem líderes sociais por causa da internalização positiva e representações cuidadas do eu e dos outros significativos. Fukada, Fukada & Hicks (1994) na sua investigação citam Segal et al (1987), em que o estilo social é um atributo da liderança para eles.…”
Section: Introductionunclassified